Victimization of Children Left Behind in Rural China. (July 2017) - Chen, Xiaojin; Liang, Ningxin; Ostertag, Stephen F.
Objectives: Examine the relationship between parental rural-to-urban migration, caretaking arrangement, and left-behind children's self-reported victimization in rural China. The direct effect of parental migration on children's victimization as well as the indirect effect through positive caretaking and children's delinquent/problem behavior involvement is explored. Methods: The study uses data from the Parental Migration and Children's Well-being Survey, which collected information on parental migration and children's experience of victimization from a probability sample of 800 middle school students in southern China. Structural equation modeling is used to evaluate hypothesized models by simultaneously assessing direct and indirect effects. Results: Compared with children living with both parents in rural China, children left behind by their fathers have an elevated level of victimization. In addition, the chronic absence of fathers leads to a higher level of delinquent and problem behavior among left-behind children, which in turn leads to further victimization. Conclusion: Left-behind children living with mothers, grandparents, or other relatives are an "at-risk" population for victimization. Local programs such as parenting lessons for left-behind parents and grandparents are needed. In addition, the importance of father's chronic absence on left-behind children's healthy physical and mental development needs to be further examined.